A Systems Approach to Minimize Wasted Work in Blockchains - Carvalho, João Pedro Lobato de (2020)
Blockchain systems and distributed ledgers are getting increasing attention since the release of Bitcoin. Everyday they make headlines in the news involving economists, scientists, and technologists. The technology invented by Satoshi Nakamoto gave to the world a quantum leap in the fields of distributed systems and digital currencies. Even so, there are still some problems regarding the architecture in most existing blockchain systems. One of the main challenges in these systems is the structure of the network topology and how peers disseminate messages between them, this leads to problems regarding the system scalability and the efficiency of the transaction and blocks propagation, wasting computational power, energy and network resources. In this work we propose a novel solution to tackle these limitations. We propose the design of membership and message dissemination protocols, based on the state-ofart, that will boost the efficiency of the overlay network that support the interactions between miners, reducing the number of exchanged messages and the used bandwidth. This solution also reduces the computational power and energy consumed across all nodes in the network, since the nodes avoid to process redundant network messages, and, becoming aware of mined blocks faster, avoid to perform computations over an outdated chain configuration.